A novel mechanism of sustained platelet αIIbβ3 activation via PEAR1 - Kauskot, Alexandre; Di Michele, Michela; Loyen, Serena; Freson, Kathleen; Verhamme, Peter; Hoylaerts, Marc F. (Blood, 2012)
Because single nucleotide polymorphisms (SNPs) in platelet endothelial aggregation receptor 1 (PEAR1) are associated with differential functional platelet responses in healthy subjects, we studied the function of PEAR1 in human platelets. During platelet aggregation by various agonists, the membrane expression of PEAR1 and its tyrosine phosphorylation increased. The recombinant PEAR1 EMI domain (GST-EMI) competitively reduced platelet adhesion to surface-coated PEAR1, diminished platelet aggregation, and eliminated PEAR1 phosphorylation. Polyclonal antibodies against the extracellular PEAR1 domain triggered PEAR1 phosphorylation in a src family kinase (SFK)–dependent manner. Such resulted in downstream signaling, culminating in extensive platelet degranulation and irreversible aggregation reactions interrupted by excess monovalent anti–GST-EMI F(ab) fragments. In resting platelets, the cytoplasmic tail of PEAR1 was found complexed to c-Src and Fyn, but on its phosphorylation, phospho-PEAR1 recruited p85 PI3K, resulting in persistent activation of PI3K and Akt. Thus, αIIbβ3 activation was amplified, hence stabilizing platelet aggregates, a signaling cascade fully interrupted by the SFK inhibitor PP1 and the PI3K inhibitor LY294002. This study is the first demonstration of a functional role for PEAR1 in platelet activation, underpinning the observed association between PEAR1 and platelet function in genome-wide association studies.